Peran Guru Pendidikan Agama Islam dalam Menanamkan Moderasi Beragama Melalui Program Kebiasaan - Rohman Heryana; Rajaminsah; Dasim (STAI Al-Mas'udiyah, 2024)
This study explores the role of Islamic Religious Education (IRE) teachers in fostering religious moderation through habitual programmes in schools. By implementing these programmes, IRE teachers aim to cultivate tolerance and mutual respect among students. The study employs a qualitative descriptive method with a literature review approach to analyse existing research and theoretical perspectives on the subject. The habitual programmes, designed and modified by teachers, include strategies to integrate moderation values into the school curriculum and daily activities. This approach not only enhances students' understanding of religious diversity but also promotes a harmonious learning environment. The findings highlight how effective these programmes are in developing inclusive attitudes and reducing religious conflicts among students. Through careful modification and implementation of these programmes, IRE teachers contribute significantly to creating a respectful and tolerant school atmosphere, preparing students to engage positively in a diverse society.